Economic inequality in Russia: problems and ways of their solution - M. L. Dorofeev (Вестник университета, 2020)
Long-term trends of inequality in leading countries of the world have been analysed. Country features of economic inequality development related to the socio-economic structure of the country and social mentality, which have a significant impact on the adjustment of the financial mechanism of redistribution of income and wealth, have been identified. The current income tax rates of 42 countries, including social insurance payments have been analysed. As a result, it has been concluded that Russia is one of the few countries with a lack ofprogressive income taxation system and very low tax rates. If our society really wants to create a strong economy similar to the European Union, China or the USA, then the first step, to introduce a progressive system of income taxation, planned in 2021 should be the basis for further accelerated implementation of an effective system of progressive taxation of income, wealth and inheritance in Russia.